2022
DOI: 10.1039/d1fo04212b
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effect of AD-1 on lipopolysaccharide-mediated fibroblast injury in L929 cells and bleomycin-induced pulmonary fibrosis in mice

Abstract: 20(R)-25-methoxyl-dammarane-3 β, 12 β, 20-triol (25-OCH3-PPD, AD-1) is a dammarane ginsenoside that is isolated from Panax notoginseng. The present study aimed to explore its anti-pulmonary fibrosis (PF) effect in vitro...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Mouse fibroblast L929 cell line, possesses characteristics similar to lung fibroblasts in terms of hyperproliferation and activation, and can be induced into myofibroblasts with TGF-β1. TGF-β1 induced L929 cells are commonly used as the cell models of lung fibrosis ( Zhang T. et al, 2020 ; Li T. et al, 2022 ; Wang et al, 2024 ). The cytotoxic effects of MR and RA were evaluated by conducting CCK-8 assays on L929 cells exposed to different concentrations (0, 10, 20, 40, 80 and 160 μM) of MR and RA ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse fibroblast L929 cell line, possesses characteristics similar to lung fibroblasts in terms of hyperproliferation and activation, and can be induced into myofibroblasts with TGF-β1. TGF-β1 induced L929 cells are commonly used as the cell models of lung fibrosis ( Zhang T. et al, 2020 ; Li T. et al, 2022 ; Wang et al, 2024 ). The cytotoxic effects of MR and RA were evaluated by conducting CCK-8 assays on L929 cells exposed to different concentrations (0, 10, 20, 40, 80 and 160 μM) of MR and RA ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are a family of enzymes that degrade collagen, and TIMPs speci cally inhibit MMPs activity. TIMP-1 not only inhibits MMPs activity and zymogen activation, but also promotes cell growth factor-like effect, which in turn promotes broblast proliferation and collagen synthesis [23]. Western blot results showed that the expressions of bronectin, collagen I, and α-SMA in the BLM group were signi cantly higher than those in the control group, and the expressions of these proteins were effectively inhibited after SIN treatment (Fig.…”
Section: Sin Alleviates Blm-induced Pf As Well As Neutralizes Ecm Dep...mentioning
confidence: 88%
“…188 Otherwise, a recent study showed that AD-1 alleviated lung fibrosis in vitro and in vivo by reducing extracellular matrix (ECM) accumulation, increasing the expression of the antioxidant enzymes SOD and GSH and regulating the TGF-β1/TIMP-1/α-SMA signalling pathway. 191…”
Section: Effects Of Ginsenosides On Pulmonary Inflammatory Diseasesmentioning
confidence: 99%